1988
DOI: 10.1071/ar9880319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminium and calcium in the soil solution of acid soils on root elongation of Glycine max cv. Forrest

Abstract: In the course of three experiments, soybean (Glycerine max (L.) Merr.) cv. Forrest was grown in 21 soils (four surface soils and 17 subsoils) amended with liming materials (CaCO3 and Mg CO3) and soluble Ca salts (CaSO4.2H20 and CaCl2.2H2O). In most soils, the soluble salts increased concentrations and activities of Al species in solution to levels that restricted root growth, and MgCO3, induced a Ca limitation to root growth. Root lengths after three days were related to so11 and soil solution attributes.Suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 36 publications
(43 reference statements)
4
50
0
4
Order By: Relevance
“…Para se elevar este pH para 6 é necessária a aplicação de aproximadamente 12 t ha -1 de calcário (Figura 5). Teor de matéria orgânica e ocupa grande parte da capacidade de troca de cátions efetiva desses solos (Camargo & Furlani, 1989). O principal fator que controla a concentração do Al na solução do solo é o pH.…”
Section: Toxidez De Alumíniounclassified
See 1 more Smart Citation
“…Para se elevar este pH para 6 é necessária a aplicação de aproximadamente 12 t ha -1 de calcário (Figura 5). Teor de matéria orgânica e ocupa grande parte da capacidade de troca de cátions efetiva desses solos (Camargo & Furlani, 1989). O principal fator que controla a concentração do Al na solução do solo é o pH.…”
Section: Toxidez De Alumíniounclassified
“…Moore Junior & Patrick (1989) concluíram que a deficiência de Ca e Mg em solos ácidos-sulfato é responsável pela diminuição da produtividade de arroz na Tailândia. Em um estudo de 17 solos da Austrália, Bruce et al (1988) Os principais fatores da planta que afetam a eficiência nutricional são: variabilidade genética, crescimento das raízes, micorrizas, fixação biológica de nitrogênio, alelopatia, doenças, pragas e plantas invasoras.…”
Section: Deficiência De Cálcio E Magnésiounclassified
“…Physiological studies with bacteria have emphasized well-known strains, such as Escherichia coli, Staphylococcus aureus, Bacillus megaterium, and Pseudomonas fluorescens (4,11,19,42,44). A broader range of studies have focused on rhizobia and documented toxicity in cultures and in bacteriumlegume symbioses (7,8,18,24,26,33,38,39,43,50,51). However, the effects of aluminum on microbes or microbial processes in a more general ecological context have not been adequately assessed.…”
mentioning
confidence: 99%
“…These values occur naturally in many soils and are increasingly common because of widespread acidification associated with acid precipitation (42). Acidification clearly mobilizes aluminum and has been associated with significant impacts on plant and animal populations (7,16,48). Whether microbial processes in soils are similarly affected is not certain.…”
mentioning
confidence: 99%
“…The amount of inorganic monomeric Al, instead of total Al, is taken as a better indicator for Al toxicity (Bruce et al, 1988). The enumeration of acid-and Al-tolerant microorganisms in acidic soils by Kanazawa and Kunito (1996) also indicated that fungi accounted for most of the highly Al resistant microorganisms.…”
Section: Effects Of Aluminium On Azotobactermentioning
confidence: 99%